Organizing Independent Education to Increase Graphic Knowledge of Students in Drawing - Nurmatov, E. A. (European Journal of Life Safety and Stability (2660-9630), 2022)
In order to develop students' knowledge and thinking, it is advisable to increase the role of independent learning outside the classroom. In the classroom, the teacher should guide the students to independent learning by providing them with a novelty and introduction to the topic, as well as resources on the topic. First of all, it increases self-discipline and responsibility.